2020
DOI: 10.1039/d0ew00279h
|View full text |Cite
|
Sign up to set email alerts
|

UVC-based advanced oxidation processes for simultaneous removal of microcontaminants and pathogens from simulated municipal wastewater at pilot plant scale

Abstract: The challenge of providing good quality reclaimed water free from contaminants of emerging concern, even at small concentrations, i.e., microcontaminants (MCs) and pathogens are main hot topics worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 69 publications
3
7
0
Order By: Relevance
“…The bacterial inactivation profiles observed in all cases obey to a double log-linear kinetic profile explained by the action of the UV-C radiation (a fast k 1 ) and the experimental setup (slower k 2 ) ( Table S3, Figure S2 ), which is similar to previous studies using the same UV-C pilot plant [ 16 ]. k 1 is attributed to the well-known efficiency of UV-C wavelengths to inactivate microorganisms in water.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…The bacterial inactivation profiles observed in all cases obey to a double log-linear kinetic profile explained by the action of the UV-C radiation (a fast k 1 ) and the experimental setup (slower k 2 ) ( Table S3, Figure S2 ), which is similar to previous studies using the same UV-C pilot plant [ 16 ]. k 1 is attributed to the well-known efficiency of UV-C wavelengths to inactivate microorganisms in water.…”
Section: Resultssupporting
confidence: 85%
“…Two water matrices were used in this study: (i) Simulated Urban Wastewater (SUWW) and (ii) Actual Urban Wastewater (UWW). SUWW was prepared following a recipe previously reported [ 16 ] as a UWW effluent model to guarantee the reproducibility and comparability of results among the different operational conditions. UWW was freshly collected from the effluent of the secondary treatment (conventional activated sludge) of the urban wastewater treatment plant of “El Bobar”, which is located in Almeria, South East of Spain, and several batches were used along the experimental plan.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning bacterial regrowth, although with 0.147 mM of S 2 O 8 2− the DL of 1 CFU/mL was reached, regrowth occurred after 24 h of the treatment, probably due to the low residual oxidant concentration (below the LOQ). This is in concordance with the results obtained by Sánchez-Montes et al (2020) [28], who reported that S 2 O 2 8− concentrations up to 0.23 mM do not prevent bacterial regrowth, because it has no bactericidal effect by itself. However, with 1.47 mM and 2.94 mM, there was no regrowth below the DL EU of 10 CFU/100 mL, the residual concentrations being 0.92 mM and 1.50 mM, respectively.…”
Section: H O + Ho • → H O + Ho •supporting
confidence: 93%